Study on Impact of Agroforestry Model to the Growth of Teak (Tectona grandis L.F) Plants - Nurheni Wijayanto (Jurnal Manajemen Hutan Tropika, 2007)
The objective of this research was to learn effect of agroforestry pattern on the growth of teak crops and the other crops. The research was conducted for 1 year in teak forest stand (1 years old) with site quality index (bonita) was 3.5. Experimental design with 10 observations per block.Blocks in this research were agroforestry pattern 1 (intercropping during the whole cycle of the main crop) and agroforestry pattern 2 (temporary intercropping). There were 2 treatments: (1) litters of corn crops were put on rows of teak crops and no fertilizers were added,(2) fertilizers were added, but litters of corn crops were taken away, and (3) fertilizers were added, and litters of corn crops were put on rows of teak crops. Area size of each observation plat was 0.05 ha. Analysis of variance on the average increament of total height of teak crop and production of dry kernel (corn seeds which had been detached from corn cob) that showed significant results were further analyzed by the use of Duncan Least Significant Difference Test. Conclusions of this research were: (1) agroforestry pattern 1 had greater effect as compared to agroforestry pattern 2 on the growth of total height of teak crop, (2) agroforestry pattern 1 had greater effect as compared to agroforestry pattern 2 on the production increase of dry corn kernels.Keywords: agroforestry, intercropping, analysis of variance, total height, production